A Local Ecosystem Assessment of the Potential for Net Negative Heavy-Duty Truck Greenhouse Gas Emissions through Biomethane Upcycling - Penny Atkins (Energies, 2021)
Decarbonising heavy-duty trucks is challenging due to high journey power and energy requirements. With a growing fleet of commercial vehicles in the UK, biomethane can provide significant reductions in greenhouse gas (GHG) emissions compared to fossil diesel. Methane is a potent GHG with a global warming potential (GWP) of 23–36, therefore reducing levels in the atmosphere can have a significant impact on climate change. There are a range of anthropogenic sources of methane that could be collected and processed to provide sustainable energy (upcycled), e.g., agricultural waste and the waste water system. This paper explores the impact of using upcycled methane in transport in South East England, evaluating local sources of anthropogenic methane and the environmental and economic impact of its use for a heavy-duty truck compared to fossil and battery electric alternatives. Analysis concludes that the use of upcycled methane in transport can provide significant reductions in lifecycle GHG emissions compared to diesel, fossil natural gas or battery electric trucks, and give net negative GHG emissions where avoided environmental methane emissions are considered. Furthermore, upcycling solutions can offer a lower cost route to GHG reduction compared to electrification.